Psychosocial Stress Among Hospital Doctors in Surgical Fields: Results of a Nationwide Survey in Germany - von dem Knesebeck, Olaf (Deutscher Arzte Verlag, 2010)
BACKGROUND: The aim of this paper is to analyze psychosocial stress in the workplace among hospital doctors working in surgical fields in Germany with the aid of the demand-control model, the effort-reward imbalance model, and selected additional indicators. METHODS: A written questionnaire was answered by a stratified random sample consisting of 1311 hospital doctors working in surgical fields in 489 hospitals in Germany. Validated instruments were used to make measurements according to the demand-control and effort-reward imbalance models. RESULTS: The working conditions of about a quarter of the hospital doctors surveyed were characterized by an effort-reward imbalance. 22% of them have “job strain” according to the demand-control model, i.e., they are confronted with high demands, yet have a low degree of control. Residents and assistant physicians not occupying training positions were both found to have an especially high degree of psychosocial stress. Furthermore, about one-fifth of the hospital doctors surveyed thought about giving up their profession at least a few times per month. 44% of them considered that the quality of patient care was sometimes or often impaired by an excessive physician workload. CONCLUSION: An investigation of psychosocial stress in the workplace among hospital doctors in surgical fields in Germany indicates that this group suffers from more severe stress at work than other occupational groups. Such working conditions pose a threat to these physicians’ own health and to the quality of the health care that they provide.